Diuretic‐sensitive electroneutral Na+ movement and temperature effects on central axons. (22nd March 2017) - Kanagaratnam, Meneka; Pendleton, Christopher; Souza, Danilo Almeida; Pettit, Joseph; Howells, James; Baker, Mark D.
Abstract : Key points: Optic nerve axons get less excitable with warming. F‐fibre latency does not shorten at temperatures above 30°C. Action potential amplitude falls when the Na + ‐pump is blocked, an effect speeded by warming. Diuretics reduce the rate of action potential fall in the presence of ouabain. Our data are consistent with electroneutral entry of Na + occurring in axons and contributing to setting the resting potential. Abstract: Raising the temperature of optic nerve from room temperature to near physiological has effects on the threshold, refractoriness and superexcitability of the shortest latency (fast, F) nerve fibres, consistent with hyperpolarization. The temperature dependence of peak impulse latency was weakened at temperatures above 30°C suggesting a temperature‐sensitive process that slows impulse propagation. The amplitude of the supramaximal compound action potential gets larger on warming, whereas in the presence of bumetanide and amiloride (blockers of electroneutral Na + movement), the action potential amplitude consistently falls. This suggests a warming‐induced hyperpolarization that is reduced by blocking electroneutral Na + movement. In the presence of ouabain, the action potential collapses. This collapse is speeded by warming, and exposure to bumetanide and amiloride slows the temperature‐dependent amplitude decline, consistent with a warming‐induced increase in electroneutral Na + entry. Blocking electroneutral Na + movement is predicted to be useful in the treatment of temperature‐dependent symptoms under conditions with reduced safety factor (Uhthoff's phenomenon) and provide a route to neuroprotection. Key points: Optic nerve axons get less excitable with warming. F‐fibre latency does not shorten at temperatures above 30°C. Action potential amplitude falls when the Na + ‐pump is blocked, an effect speeded by warming. Diuretics reduce the rate of action potential fall in the presence of ouabain. Our data are consistent with electroneutral entry of Na + occurring in axons and contributing to setting the resting potential.